Principal Leadership in Implementing Independent Learning to Increase Teacher Awareness - Kusumawati, Erna (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
The purpose of this study was to examine the role of principals in increasing teacher awareness regarding the implementation of Merdeka Belajar (Freedom to Learn). Based on the educational transformation towards autonomous learning, this study analyzed successful leadership strategies. The results of a combination of quantitative (survey) and qualitative (interview, observation) methods indicate that professional support, principal capacity building, and transformational leadership significantly improved teacher understanding and commitment. Principals successfully transformed teachers' roles into facilitators by serving as role models, inspiring, stimulating intellectually, and providing individualized attention. They also facilitated workshops and coaching. This research contributes to the development of educational leadership and pedagogical models and provides practical suggestions for teacher and principal development programs that support an adaptive, science-and-technology-based education ecosystem.